Pengaruh penambahan proporsi tepung wortel (Daucus carota L.) dan lama pendinginan terhadap kualitas mikrobiologi bakso daging ayam - Andik Dwi Purnomo; Muh. Aniar Hari Swasono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
This study aims to determine the effect of adding the proportion of carrot flour and cooling time on the microbiological quality of chicken meatballs and to determine the proportion of the best carrot flour added to chicken meatballs on microbiological and organoleptic quality. The method used in this research was randomized block design (RAK), which had 2 treatments, namely the addition of carrot flour to tapioca flour (0%, 25%, 50% and 75%) and cooling time (3 days and 5 days). The tests carried out included microbiology (pH, total plate count, total coliform, total yeast and mold) and organoleptic tests (taste, color, aroma, texture). The data obtained were analyzed using ANOVA statistical analysis using Minitab software and followed by the Tuckey difference test, while the organoleptic parameters were analyzed using the Fridmen test. The results of the study based on microbiological tests showed the best treatment according to the Zeleny method in L1W3 treatment (3 days cooling time; 25% tapioca flour: 75% carrot flour). The results of microbiological research showed that with pH (6.55), total plate count (0, 12 log10²cfu / gr), total coliform (0.03 log10²cfu / gr), total yeast and molds (0.17 log10²cfu / gr), and organoleptic taste 2.72 (neutral), aroma 2.92 (neutral), color 3 , 08 (neutral) and texture 3 (neutral). The results of the study based on the Organoletic test showed that the best treatment was in the L1W1 treatment (3 days cooling time; 75% tapioca flour: 25% carrot flour) the results of organoleptic research showed that with the provisions of pH (6.55), total plate count (1.43 log10²cfu / gr), total coliform (1.15 log10²cfu / gr), total yeast and mold (2.33 log10² cfu / gr), and organoleptic taste 3 (neutral), aroma 3.96 (like), color 3.64 (like ) and textures 2.32 (disliked).